The highly conserved intron of tyrosine tRNA is critical for m1 A58 modification and controls the integrated stress response - Catherine J. Stuart; Jennifer E. Hurtig; Talia Tzadikario; Niki K. Thomas; Miten Jain; Ambro van Hoof (Proceedings of the National Academy of Sciences, 2025)
tRNA introns are a universally conserved feature of eukaryotic genomes, but the reason for their conservation has remained obscure. We have previously shown that a defect in the essential tRNA splicing endonuclease of yeast results in transcriptome remodeling, resembling that of the integrated stress response (ISR). In this study, we show that ISR activation in this mutant requires the canonical ISR components, including the collided ribosome sensor Gcn1. We further show that splicing of tyrosine tRNA, but not splicing of any of the other intron-containing tRNAs, controls the ISR. Using nanopore direct RNA sequencing, we show that the intron of tyrosine tRNA affects m1 A58 modification in the T arm loop of the mature tRNA. In support of these results, we show that deletion of either subunit of the enzyme that adds the m1 A58 modification also controls the ISR. Unlike the few intron-dependent modifications previously described, the intron-dependent m1 A58 modification site is distal from the intron and has a clear physiological impact. Finally, we survey the occurrence of tRNA introns in eukaryotic genomes and show that the tyrosine tRNA intron is more prevalent than any other tRNA intron. These data suggest that tRNA splicing is conserved in eukaryotes because hypomodified tyrosine tRNAs lead to collided ribosomes, resulting in stress to cell physiology.